Analisis Efektivitas Marka Kotak Kuning Di Simpang Tiga Jalan Soekarno Hatta – Jalan Arifin Ahmad Kota Pekanbaru - Muchammad Zaenal muttaqin; Abdul Kudus Zaini; Zhella Indah Saviri (Lentera Dua Indonesia, 2022)
One of the interchanges in Pekanbaru City, namely simpang tiga (Jalan Soekarno Hatta - Jalan Arifin Ahmad) has quite dense activities, because this road is an access to the center of community activities to the market area, offices and others. An increase in the number of vehicles larger compared to the available roads leads to congestion. One of the efforts to reduce congestion at intersections is to use yellow box markings. This marking is designed as a vehicleless area, if there is a traffic congestion, vehicle users who are still outside the marking must stop and wait until the traffic jam breaks down. This study aims to analyze the effectiveness of the yellow box markings and the suitability of the yellow box markings. This study used the Regulation of the Minister of Transportation No. 34 of 2014 and the Traffic Signs Manual Chapter 5 Road Markings (2018) and the Indonesian Road Capacity Manual (MKJI) 1997 to determine the effectiveness of intersection performance. The parameter used to determine the effectiveness of interchange performance is the degree of saturation. The results of the analysis found that the size of the yellow box markings at the research site was not appropriate according to Permenhub No.34 of 2014 the width of the straight line and the diagonal line was 10-18 cm and the Traffic Signs Manual Chapter 5 Road Markings (2018) the width of the diagonal line was 15 cm and the width of the straight line was 20 cm, while at the research location the width of the straight line and the diagonal line was 30 cm. For the number of offenders the yellow box markings were 7195 offenders. Based on the results of the saturation degree analysis, for intersection three, the saturation degree value exceeds 1.00 which indicates that the yellow box marking is not effective in improving the performance of the intersection.